Health Complaints Associated With Poor Rental Housing Conditions in Arkansas: The Only State Without a Landlord's Implied Warranty of Habitability - Horwitz-Willis, Nathaniel (Frontiers in Public Health, 2018)
This is a review of an existing article that surveyed the perceived health of renters' in Arkansas. As a first in the field of public health it was able to provide ground-level insight through tenant interviews about housing and health in the state. This review illuminates how the state's sociopolitical characteristics may affect marginalized Arkansas renters. Marginalized renters may include persons living below the poverty line, people of color, and women who are the head of household. This article seeks to elucidate how the upstream factor, habitability law, may impact tenant health in the state. With a novel public health approach, the article contributes to the existing housing and health literature with its invaluable insight of stakeholders' perspectives relating to how habitability law may impact their health outcomes. Now is an opportune time for public health practitioners, researchers, and policymakers to facilitate incremental change to include landlords in their state public health system. Such inclusion may improve housing while promoting, improving, and protecting health outcomes for Arkansas renters.